A CIPHERTEXT-POLICY ATTRIBUTE-BASED SEARCHABLE ENCRYPTION SCHEME IN NON-INTERACTIVE MODEL - Trinh, Van Anh; Trinh, Viet Cuong (Journal of Computer Science and Cybernetics, 2019)
We address the problem of searching on encrypted data with expressive searching predicate and multi-writer/multi-reader, a cryptographic primitive which has many concrete application scenarios such as cloud computing, email gateway application and so on. In this paper, we propose a public-key encryption with keyword search scheme relied on the ciphertext-policy attribute-based encryption scheme. In our system, we consider the model where a user can generate trapdoors by himself/herself, we thus can remove the Trusted Trapdoor Generator which can save the resource and communication overhead. We also investigate the problem of combination of a public key encryption used to encrypt data and a public-key encryption with keyword search used to encrypt keywords, which can save the storage of the whole system